Family involvement in faith-based schools - Hiatt-Michael, Diana B. (Family, school, community, partnership., 2017)
An essential read for all school principals and persons engaged in educational policy. Parental interest in faith-based schooling for children has surged and the contents of this book reveal the reasons for this surge. This book provides insights to school choice, support for faith-based schooling, and opening doors for increased parent involvement in schools.Authors focus on promising practices that these schools utilize to engage parents in the daily life of school and the effects of such practices on the educational life of the school. Their work cover Catholic, Jewish, Christian and Muslim schools within the U. S. and internationally. In addition, chapters suggest ways to market schools and promote social justice in faith-based schools.